Nutrient and antioxidant profile of four species of wild mushrooms from cold-desert with implications for human dietary and supplement use - Hom-Singli Mayirnao; Pooja Jangir; Karuna Sharma; Surinder Kaur; Yash Pal Sharma; Rupam Kapoor (Food Chemistry Advances)
Extreme environmental conditions in cold deserts modulate the biochemical profile of organisms thriving therein, translating into nutritional benefits for humans. This study assessed nutritional composition and antioxidant potential of four wild edible mushroom species—Volvariella bombycina, Tricholoma cingulatum, Coprinus comatus, and Bovista plumbea— from the Trans-Himalayan region of Kargil. Metabolic profiling identified sugars, polyols, organic acids, and fatty acids, with sugars and their derivatives dominating the metabolite composition (33.40–50.90 %). Trehalose (13.68–27.93 %) and glucitol (3.71–10.33 %) were especially abundant. Linoleic acid (2.50–7.63 %) was the most prevalent essential polyunsaturated fatty acid. Total protein content ranged from 122.50–312.01 mg/g dry weight, with various essential amino acids detected. The mushrooms demonstrated high bioavailability of minerals— Fe, Cu, Mg, and Ca— imputable to low antinutrient concentrations. C. comatus exhibited the highest enzymatic activities for superoxide dismutase, peroxidase, and glutathione peroxidase, while B. plumbea demonstrated the highest catalase activity and concentrations of non-enzymatic antioxidants including phenolics, flavonoids, ascorbic acid, and α-tocopherol. V. bombycina exhibited maximum carotenoid-based antioxidants. Antioxidant assays indicated C. comatus as the strongest radical scavenger (IC50=7.92) and V. bombycina with the highest reducing power (IC50=5.71). The study highlights the potential of these mushrooms as a source of nutraceuticals and dietary supplements.